Country of origin and brand image influences on perceptions of online game quality. Issue 6 (2nd November 2015) - Kim, Sang Jin; Choi, Yung Kyun; Kim, Kyung Hoon; Liu, Honglei
Abstract: The authors of this study investigate online game consumption in Korea and China, the two key Asian markets, to analyze relationships among country of origin (COO), brand image, belief toward online games, and perceived game quality. Perceived game quality includes three dimensions of quality: product quality, service quality, and gratification quality. The authors survey 355 Korean and Chinese online game users and find that brand image influences quality perceptions directly or indirectly through brand belief. Compared with brand image, COO seems to have indirect and weaker effects on perceptions of game quality. The multigroup research model reveals several cross‐country differences. COO significantly affects beliefs in China but not in Korea. Brand image more highly impacts brand beliefs in Korea than it does in China. To signal superior product or service quality to Chinese users, game developers should highlight COO along with other product information. To appeal to Korean users, game developers should strengthen symbolic aspects of brand image because Koreans react more positively to brand personality, brand content, and corporate identity. Copyright © 2015 John Wiley & Sons, Ltd.